Análisis de la producción pecuaria en la región San Martín, período 2008-2015 - Marín Córdova, Wilson (2017)
The main objective of this research is to carry out an analysis of the production in the livestock subsector of the San Martín region, during the period 2008-2015. The importance of this research is that it allows us to have an idea of the factors that constitute determinants of livestock production in the region. The present work poses the following problem: What is the behavior of livestock production in the San Martin region during the 2008-2015 period? The hypothesis formulated maintains that the production of the livestock subsector of the San Martin region has a growing behavior associated with determinant factors such as teamwork with producers organized through production chains, using appropriate technologies and means to increase productivity and competitiveness in the region during the period 2008-2015. The present investigation has a non experimental character, to develop it, we resorted to statistical sources that have allowed us to obtain data for its subsequent analysis throughout the period studied. It is concluded that livestock production in the San Martin region has shown an increase, as a result of the effective productive strategies that have been established, and implemented, consciously to the present.